Hypocholesterolemic efficacy of royal jelly in healthy mild hypercholesterolemic adults - Hui-Fang Chiu; Bo-Kai Chen; Yan-Ying Lu; Yi-Chun Han; You-Cheng Shen; Kamesh Venkatakrishnan; Oksana Golovinskaia; Chin-Kun Wang (Taylor & Francis Group, 2017)
Context: Royal jelly (RJ) has been reported for its health promoting factors such as antioxidant, anti-inflammatory and lipid lowering activities. Objective: The present randomized, placebo-controlled study examines the hypolipidemic beneficial effect of RJ through evaluating anthropometric measurements, lipid profile and various hormone levels in mildly hypercholesterolemic participants. Materials and methods: Forty subjects with mild hypercholesterolemia (180-200 mg/dL) were randomly selected and divided into two groups as experimental or placebo, who requested to intake nine capsules (350 mg/capsule) of RJ or placebo/day, respectively, for three months with one month of follow-up without any supplementation. Results: No significant changes were noted in any of the anthropometric parameters like body weight, waist and body fat. The serum total cholesterol (TC; 207.05-183.15 mg/dL) and low-density lipoprotein cholesterol (LDL-c; 126.44-120.31 mg/dL) levels were reduced significantly (p < 0.05) after administration of RJ. However, triglyceride (TG) and high-density lipoprotein cholesterol (HDL-c) levels were not considerably altered. Moreover, three months of RJ consumption significantly ameliorated (p < 0.05) the concentration of sex hormones like dehydroepiandrosterone sulphate (DHEA-S; 1788.09-1992.31 ng/mL). Also, intake of RJ did not elicit any hepatic or renal damage. Discussion and conclusion: Intervention with RJ for three months considerably lowered the TC and LDL-c levels through improving the levels of DHEA-S and thus alleviates the risk of cardiovascular disease (CVD).